Luminescent hybrid metal-organic coordination polymers based on Cu/Ag-bis(benzotriazole) units and polyoxometalates. Issue 11 (2nd July 2016) - Sun, Meng; Zhou, Wen-Zhe; Wang, Yong-Hui; Tan, Hua-Qiao; Qi, Yan-Fei; Zang, Hong-Ying; Li, Yang-Guang
Abstract: The reaction of polyoxometalate (NH4 )6 [Mo7 O24 ], transition-metal ions (Cu 2+ or Ag + ), and a bridging ligand (bbtx) in the hydrothermal environment led to two hybrid coordination polymers, [Cu(bbtx)3 ][Mo6 O19 ] (1 ) and [Ag2 (bbtx)2 ][Mo6 O19 ] (2 ). Luminescent measurements suggest that1 mainly exhibits luminescent emission of bbtx, but2 displays strong emission bands ascribed to the ligand-to-metal charge transfer. Compound2 also shows reversible thermochromic luminescence from 300 K–77 K–300 K. Introduction of [Mo6 O19 ] 2− into the Ag-bbtx network can lead to luminescent quench of2 under irradiation of 300 W Xe light, due to reduction of Ag(I) into Ag(0) with breaking of Ag–N bonds of2 . The relevant mechanism was investigated by Powder X-ray diffraction and X-ray photoelectron spectrum, and the irradiated2 was used as a catalyst for reduction of p-nitrophenol with good catalytic activity. Abstract :